Kajian Lingkungan Hidup Strategis Dalam RPJMD Sebagai Upaya Pencegahan Pencemaran atau Kerusakan Lingkungan Hidup di Kabupaten Rokan Hilir Berdasarkan Undang- Undang Nomor 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup - Muzzani '; Emilda Firdaus; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Law of the Republic of Indonesia Number 32 Year 2009 on the protection and Environmental Management in Rokan Hilir. Carrying capacity and the capacity exceeds that should, as well as the ineffectiveness of the SEA in Rokan Hilir RPJMD be one of the issues that have a major impact on development in Rokan Hilir. Therefore the aim of this Thesis Writing: first, how the implementation of the Strategic Environmental Assessment (SEA) in RPJMD in Rokan Hilir by Act No. 32 of 2009 on the Protection and Environmental Management. second, how the effectiveness of the Strategic Environmental Assessment (SEA) in RPJMD in Rokan Hilir. Third, if the efforts to be made towards the implementation of the Strategic Environmental Assessment in RPJMDdi Rokan Hilir.This type of research can be classified in this type of empirical legal research or sociological, Because in this study the authors directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted in BAPEDALDA office, in the office of Planning, and in the office of Spatial Rokan Hilir. Population and Sample is chairman of the Regional Environmental Management Division of Rokan Hilir, head of Management of Regional Development of Rokan Hilir, chairman of the Department of Spatial Planning Rokan Hilir, Head of Mining and Energy and the Environment Rokan Hilir, Chairman of field development planning Rokan Hilir. Source of data used, namely: primary data and secondary data. Data collection techniques in this study by observation, interview, and literature study.The conclusion that can be derived from the results of the first study, how the implementation of the Strategic Environmental Assessment (SEA) in RPJMD in Rokan Hilir by Act No. 32 of 2009 on the Protection and Environmental Management did not materialize. second, how the effectiveness of the Strategic Environmental Assessment (SEA) in RPJMD in Rokan Hilir ineffective because the budget factor, the factor of human resources, community factors, factors not the implementation of SEA in RPJMD in Rokan Hilir Year 2011-2016, Quality Control Implementation of SEA in the preparation of Rokan Hilir RPJMD 2011-2016. Thirdly, the Government of Rokan Hilir should be more creative to find sources of income and do the regulations and policies that pro against the people in the plantation sector, oil and gas, prepare and provide specialized training for human resources more reliable in the face of environmental problems and improve public awareness to comply with a rule of law.Keywords: Implementation of SEA in RPJMD-Sustainable Development-Rokan Hilir